Pelatihan Kelayakan dan Pendampingan Pendirian Usaha BUMDES di Desa Jatibatur Kabupaten Sragen - Anik Munawaroh; Ratna Trihastuti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
The purpose of this activity is to assist village officials and the people of Jatibatur Village, Gemolong District, Sragen Regency in making village economic programs (microeconomics) in utilizing village potential through BUMDES. In addition, it also aims to assist and help understand the feasibility study/plan for establishing a business in the BUMDES Jatibatur Village. The implementation of training and mentoring, especially for BUMDES members in Jatibatur Village, Gemolong District, Sragen Regency, was carried out using lecture, tutorial, and discussion methods. The methods for implementing this service activity are as follows: 1) lecture method: participants are given motivation to have the will to establish a Village Owned Enterprise (BUMDES), 2) tutorial method: training participants are given material on the establishment process, and 3) discussion method: training participants given the opportunity to discuss problems related to the establishment of Village Owned Enterprises (BUMDES) that have been faced so far. The result of the implementation of service is the actualization of knowledge and knowledge to the community, especially rural communities who need assistance. Village officials and village communities jointly explore the potential of the village to be used as economic efforts for welfare, so that the realization of BUMDES in Jatibatur Village.